Impact of the recovery of vegetation, and vigilance and monitoring of protected areas programs of The Fund for the Protection of Water, Quito-Ecuador - Coronel Tapia, L. (2009)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica),2009